Hepatitis D virus RNA editing: specific modification of adenosine in the antigenomic RNA. - Casey, J L (1995)
RNA editing plays a central role in the life cycle of hepatitis D virus (HDV), a subviral human pathogen. Previous studies (J.L. Casey, K.F. Bergmann, T.L. Brown, and J.L. Gerin, Proc. Natl. Acad. Sci USA 89:7149-7153, 1992; H. Zheng, T.-B. Fu, D. Lazinski, and J. Taylor, J. Virol. 66:4693-4697, 1992) had concluded that the genomic RNA of HDV was the target for RNA editing and that the editing reaction was a conversion of U to C. However, we show here that the antigenomic RNA of HDV is in fact the target for HDV RNA editing, which is therefore a conversion of A to G. This result is verified by using an assay specific for editing on the antigenomic RNA and by analyzing the editing of site-directed mutant RNAs in transfected cells and in cell extracts. Because editing occurs in the absence of viral antigens and the specificity for the HDV editing target site is present even in extracts from Drosophila cells, it is likely that HDV RNA is edited by one or more cellular factors that are conserved among higher eukaryotes. These results raise the likelihood that double-stranded RNA adenosine deaminase specifically edits HDV antigenomic RNA.